Different countries – different people : countries, peoples and nations in textbooks for Year 1–3 students between 2000 and 2020 - Landau-Czajka, Anna (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2021)
The article aims to show the patterns and changes that occur in teaching about continents, countries and their inhabitants in school textbooks at the level of primary school education. It analyses selected textbooks for Year 1–3 students, published in the 21st century, with particular emphasis on the most popular series. The study presents examples of characteristic narratives that appear in textbooks, with an indication of which of them are prevalent and which appear only occasionally. It exposes the problems of the contemporary Polish school, such as Eurocentrism, Polonocentrism and the reproduction of stereotypes about the ‘Others’. Although the official message in the core curriculum and school textbooks is unequivocal: everyone, regardless of skin colour or nationality, is equal, in practice, the curriculum content and textbook illustrations clearly divide the world into wealthy and modern ‘Us’ and the poor and backward Third World. The ‘Others’ are presented as an exotic, even wild element, needy of assistance from the citizens of the civilised countries. The author draws attention to the dangers associated with underestimating the richness of the multiethnic and multicultural world and failing to notice the diversity of its population, different cultures and educational systems present on different continents and in different countries.
Keywords: textbooks; primary school education; core curriculum; eurocentrism